2014
DOI: 10.1016/j.sleep.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Objective sleep, a novel risk factor for alterations in kidney function: the CARDIA study

Abstract: Objective To determine the association between objectively measured sleep and 10-year changes in estimated glomerular filtration rate (eGFR). Methods From 2003 to 2005, an ancillary sleep study was conducted at the Chicago site of the Coronary Artery Disease in Young Adults (CARDIA) study. Community-based black and white adults (aged 32–51 years) wore a wrist actigraph up to six nights to record sleep duration and fragmentation. Sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
1
36
1
2
Order By: Relevance
“…The second, substantially smaller prospective study of 463 adults found that the adjusted risk of a 10-year decline in eGFR of >3% was 0.83 (95% CI 0.64 – 1.08) per additional hour of sleep per night; this potential benefit from additional sleep (or, reciprocally, a determent from less sleep) was not statistically significant, possibly due low statistical power. (15) Consistent with their observations, we found that shorter sleep duration was significantly and independently associated with faster annualized decline in eGFR and a greater risk of having a ≥30% decline in eGFR at 11 years.…”
Section: Discussionsupporting
confidence: 91%
“…The second, substantially smaller prospective study of 463 adults found that the adjusted risk of a 10-year decline in eGFR of >3% was 0.83 (95% CI 0.64 – 1.08) per additional hour of sleep per night; this potential benefit from additional sleep (or, reciprocally, a determent from less sleep) was not statistically significant, possibly due low statistical power. (15) Consistent with their observations, we found that shorter sleep duration was significantly and independently associated with faster annualized decline in eGFR and a greater risk of having a ≥30% decline in eGFR at 11 years.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies had investigated the association between sleep and kidney health outcome. Both short and long sleep duration were reported to be associated with decreased eGFR and the progression to ESRD among CKD 12, 21, 32, 33 or hypertension 18 population, and to be associated with increased eGFR, hyperfiltration, inadequate hydration and the prevalence of CKD among community-based general population 13, 19, 20, 2628 . In our study, based on same general community population, we further demonstrated that inappropriate sleep duration had converse effects on eGFR in healthy or early-stage nephropathy population, which was consistent to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of studies suggested extreme sleep duration may contribute to the decline of kidney function, which is closely tied to the vascular system, also an important, independent risk factor for cardiovascular disease. Both extremely short 11, 12 and long 13 sleep duration and poor sleep quality 14, 26 were reported to be related to higher urine albumin-to-creatinine ratio(UACR), which is a sensitive indicator for microalbuminuria or early stage of kidney damage, among US and Japanese population. In addition, short sleep duration was associated with higher odds of inadequate hydration 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendation is 7 to 9 hours for optimal health (Consensus Conference, ). Previous research has shown that shorter sleep reduced kidney function and filtration rate 10 years later (Petrov et al, ). However, few studies have examined how sleep duration is associated with hydration status beyond anecdotal reports of sleep‐restricted participants reporting trouble with blood draws due to dehydration (Opstad, ).…”
Section: Life Course Changes and Interactions With Health Conditions mentioning
confidence: 99%